ANALISIS PERAN MANAJEMEN PENDIDIKAN BERBASIS MULTIKULTURAL DALAM MENGURANGI DISKRIMINASI DAN BULLYING DI SEKOLAH DASAR - Firdha Halizah; Najwa Haya Karin; Reisha Ayu Maharani; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
This research is motivated by the need to understand and address the problems of conflict, deviant behavior, and bullying cases in the elementary school environment, as well as to implement effective classroom management strategies and create an inclusive learning environment. The purpose of this study is to identify the factors that affect the successful implementation of classroom management, educational programs, and the establishment of an inclusive environment in the context of elementary schools. This research method uses literature studies to collect and analyze information from articles, books, and previous research related to the implementation of management strategies in the context of education, with the aim of concluding and presenting data on management strategies that can improve the quality of education. The results of the study show that effective classroom management is very important in creating an inclusive learning environment in elementary schools. Intervention programs such as the Bullying Prevention Program have proven their effectiveness in reducing bullying incidences, while inclusive education has a role to play in reducing the level of discrimination and building more tolerant student character. The implication is that a multicultural approach to education management not only minimizes bullying incidents, but also creates a safe and supportive school environment for all students